Agama dan Etnisitas di Pentas Politik Lokal (Tinjauan Terhadap Penggunaan Simbol Agama dan Etnis dalam Pilkada) - Hasbullah Hasbullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The party of democracy (Pilkada) have role which potential baffle, because result and process of the implementation will give impact to adult education of society politics and development in autonomous era. At one side, direct Pilkada earn more is drawing near of candidate with all its elector as well as can grow the spirit of and tradition democratize until to undertow. On the other side, direct Pilkada also can exploit local strength in reaching for victory in local political stage. As nation which is plural, issue of primordial - religion and is ethnic - not yet earned to be overruled. More than anything else all elector of this nation still pertained traditional elector. All local political elite always exploit religion symbols and ethnical in execution of campaign and reach for sympathy of elector. The candidate also consider religion and ethnicity in chosening its couple candidate, because from some result of study show brotherhood tying and network of family is also made as society preference in chosening.